EFEKTIVITAS PEMBELAJARAN PENANAMAN NILAI-NILAI KARAKTER SOSIAL SISWA DALAM PEMBELAJARAN PAI DI SMA AL-HIDAYAH MEDAN - Subban Lubis (Universitas Islam Negeri Sumatera Utara Medan, 2019)
Character is one of the goals of education today. One character that needs to be instilled in high school students is social character. Therefore, this study aims to find out: 1) Social character phenomena that occur in students at Al-Hidayah Medan High School. 2) PAI teacher activities planning Islamic Religious Learning in the inculcation of social character values in students at Al-Hidayah Medan High School. 3) Islamic religious learning in instilling the values of social character in students at Al-Hidayah Medan High School. 4) Evaluation of Islamic Religious Learning in instilling the values of social character in students in Al-Hidayah Medan High School. The research method uses qualitative research, namely research conducted naturally by utilizing researchers as research instruments. The subjects of this study were PAI teachers, school principals, and Al-Hidayah Medan High School students. Data retrieved through observation, documentation, and interviews. Data are analyzed based on data reduction, data presentation, and conclusions drawing. The results of this research can be concluded as follows: 1) The phenomenon of social character displayed by students at Al-Hidayah Medan High School is mutual cooperation, respect, mutual reminding, mutual appreciation, helping each other in distress. 2) PAI learning planning conducted by PAI teachers in PAI learning in instilling the values of social character in Al-Hidayah Medan High School is to prepare RPP at the beginning of the semester taking into account compilation standards, core competencies, vision and mission and school goals as well as students' needs, here students, and activities that are close to the daily lives of students. PAI teachers prepare lesson plans at the beginning of the semester and are reported at teacher meetings to get input from peers and school principals. 3) Constraints experienced by PAI teachers in developing lesson plans are habitual factors. The teacher does not really understand how to match the demands of compilation standards and core competencies with the needs of students and make them using appropriate learning methods and learning media. 4) The learning process of PAI in instilling the values of social character of students in Al-Hidayah Medan High School is carried out with exemplary learning methods, role playing, giving examples, lectures, discussions, and observations. The learning method used is interesting to be followed by students, and students can be enthusiastic in following the learning process carried out. 5) Evaluation of learning towards learning that takes place at Al-Hidayah Medan High School is carried out with daily tests, giving homework, midterm, and final exam. In practice, students get high scores above the minimum completeness criteria value of 85.Keywords: PAI learning, social character